Thermo-oxidative stability of asymmetric distigmasterol-modified acylglycerols as novel derivatives of plant sterols. (1st October 2022) - Rudzińska, M.; Olejnik, A.; Grygier, A.; Kowalska, K.; Kmiecik, D.; Grudniewska, A.; Chojnacka, A.; Gładkowski, W.; Maciejewska, G.; Przybylski, R.
Highlights: For increased stability of phytosterols, new structured lipids were synthesized. Thermo-oxidative degradation of new distigmasterol-acylglycerols was determined. Polar and nonpolar oxidation products formed during heating were determined. New acylglycerols offered better stability compared to stigmasterol and its esters. Heated new structured lipids with a succinic linker didn't show cytotoxicity. Abstract: The study investigated the thermo-oxidative stability of distigmasterol-modified acylglycerols as a new structured acylglycerols. Samples were heated at 60 and 180 °C for 8 h. Their percentage degradation and products formed during heating were compared with free stigmasterol and stigmasteryl esters. The remaining of stigmasterol and fatty acid parts, the formation of stigmasterol oxidation products and the composition of polar and non-polar fractions were analysed using chromatographic methods. The cytotoxicity and genotoxicity were determined with the use of an MTT test and a comet assay, respectively. The highest stability during heating was observed for 2, 3-distigmasterylsuccinoyl-1-oleoyl- sn -glycerol (dStigS-OA) and the lowest for 2, 3-distigmasterylcarbonoyl-1-oleoyl- sn -glycerol (dStigC-OA). Data showed that the formation of thermo-oxidative degradation products is affected by the temperature and chemical structure of lipids present in the molecule. The dStigMAs bonded by a succinate linker and products formed during their thermo-oxidation showed no cytotoxic or genotoxic activity to normal human cells.